Implementasi Metode Phonetic Placement pada Gangguan Artikulasi Klien Down Syndrome: Studi Kasus Tunggal - Lestari, Nining; Muhammad Jamal, Ibrahim; Talitha Tsania, Azza Talitha Tsania; Bintari, Hana (Akademi Terapi Wicara, 2023)
down syndrome is the most common chromosomal disorder that causes intellectual disability. Articulation disorder is one of the symptoms found in down syndrome. The condition is affected by macroglossia, muscle hypotonia, lack of control over lips and tongue and motor deficiency. The need for early intervention through speech therapy, physiotherapy, and occupational therapy as well as medical attention for various health problems that occur.